Smart Hubs – A network of multifunctional urban objects to support micromobility in Ferrara - Ilaria Fabbri (Agathón)
The investigated topic is highly relevant as it addresses the challenges of sustainable mobility, the provision, and management of local services. This contribution outlines principles and outcomes of the implementable urban installation project currently being tested in Ferrara, aimed at enhancing the charging infrastructure for small electric vehicles and monitoring air quality. These pilot urban installations, referred to as Smart Hubs, incorporate multi-level modularity, facilitating their production, installation, and maintenance. What is highlighted as the most original aspect is the creation of a multifunctional system capable of ‘organising’ urban objects that increasingly accumulate with heterogeneity in public spaces, making them customisable, open to community input, and responsive to local needs expressed during a co-creation process.